Coastal Engineering 2004 2005
DOI: 10.1142/9789812701916_0219
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sediment Transport Formulation on the Linear Stability of Planar and Barred Coasts

Abstract: The linear stability of a planar and a barred coast is studied with a complex processbased model. By applying either the Engelund and Hansen or the Bailard sediment transport formulation, and a wave angle of approximately 5° in the breaker zone, the sensitivity of the linear stability characteristics to the sediment transport formulation is explored. Applying Engelund and Hansen to planar beaches, no fastest growing mode is found since the growth rate continuously increases with increasing wavelength. The corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
3
5
0
Order By: Relevance
“…This conclusion is supported by findings of Klein et al [2004] and M. D. Klein and H. M. Schuttelaars (Morphodynamic evolution of double‐barred beaches, submitted to Journal of Geophysical Research , 2005) (hereinafter referred to as Klein and Schuttelaars, submitted manuscript, 2005) for barred beaches. In the work of Klein et al [2004] it was shown that the linear stability characteristics of barred beaches are far much less sensitive to the sediment transport formulation, although significant differences between the preferred spacings obtained with Engelund and Hansen [1967] and Bailard [1981] exist.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…This conclusion is supported by findings of Klein et al [2004] and M. D. Klein and H. M. Schuttelaars (Morphodynamic evolution of double‐barred beaches, submitted to Journal of Geophysical Research , 2005) (hereinafter referred to as Klein and Schuttelaars, submitted manuscript, 2005) for barred beaches. In the work of Klein et al [2004] it was shown that the linear stability characteristics of barred beaches are far much less sensitive to the sediment transport formulation, although significant differences between the preferred spacings obtained with Engelund and Hansen [1967] and Bailard [1981] exist.…”
Section: Discussionsupporting
confidence: 55%
“…This conclusion is supported by findings of Klein et al [2004] and M. D. Klein and H. M. Schuttelaars (Morphodynamic evolution of double‐barred beaches, submitted to Journal of Geophysical Research , 2005) (hereinafter referred to as Klein and Schuttelaars, submitted manuscript, 2005) for barred beaches. In the work of Klein et al [2004] it was shown that the linear stability characteristics of barred beaches are far much less sensitive to the sediment transport formulation, although significant differences between the preferred spacings obtained with Engelund and Hansen [1967] and Bailard [1981] exist. The predictive capabilities of linear stability analyses of barred beaches for the temporal evolution of these beaches and a comparison with observations is made by Klein and Schuttelaars (submitted manuscript, 2005), showing that the results of the LSAs are only a good prediction of the bed forms and their orientation, length scales and migration rates in the initial phase of the temporal evolution.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Two different sediment transport descriptions are used since existing linear stability analysis suggests that the type of sediment transport can have a profound influence on the shape of the emerging bars (Ribas et al 2003). This is particularly true in the case of an unbarred beach and has motivated the choice of an unbarred beach for our study (Klein et al 2004). The formulation of the so called morfo55 model and the basic states are described in § 2.…”
Section: Introductionmentioning
confidence: 99%